TANTANGAN DAN SOLUSI PEMBELAJARAN HADITS KELAS 1 SD DI SD-IT PUTRI ABU HURAIRAH MATARAM: STUDI KASUS PRAKTIK PENGALAMAN LAPANGAN - Nur Shabrina Hanifati; Widiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the main challenges faced by student teachers during their Field Experience Practice (PPL) in delivering Hadith lessons, as well as to identify effective solutions and strategies implemented at SD-IT Putri Abu Hurairah Mataram. Hadith instruction is an essential subject in Integrated Islamic Elementary Schools (SD-IT), requiring creative teaching methods to ensure that students understand and memorize the material effectively. This research employs a qualitative case study approach with a descriptive method, based on observations, reflections, and daily notes recorded by PPL students during the even semester of the 2025/2026 academic year. The findings reveal several key challenges in teaching Hadith, including: (1) The PPL period coincided with the Mid-Semester Summative Assessment (STS), which divided students’ focus and motivation; (2) Classroom management during high-concentration materials; and (3) Limited teaching strategies by the student teachers. To overcome these obstacles, PPL students implemented several strategic solutions, such as: (1) Applying the Talqin method combined with repetition (Murojaah Jama’i) to reinforce memorization; and (2) Utilizing audio-visual media (e.g., YouTube) to contextualize Hadith and make lessons more engaging. The study concludes that successful Hadith learning amid these challenges requires adaptive and innovative teaching, particularly by integrating traditional methods with digital tools. These findings are expected to offer practical insights for future PPL programs and serve as a useful reference for Islamic education teachers seeking to enhance the quality of Hadith instruction in Islamic elementary schools.